2022
DOI: 10.1108/bij-01-2022-0019
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of mobile apps adoption by retail investors for online trading in emerging financial markets

Abstract: PurposeThe purpose of this study is to investigate the influence of mobile applications on investment decisions by retail investors in stocks and mutual funds. This study focuses on how mobile technologies are applied on mobile apps by retail investors for e-trading in emerging financial markets.Design/methodology/approachThe study explored predictive relevance for the adoption behavior of retail investors under the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. Further, goal contagion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 118 publications
0
3
1
Order By: Relevance
“…The statistical test results show a p-value of 0.449 and a path coefficient value of -0.019, which indicates that H3 is rejected. These results contradict research from Nair et al (2023), which states that social influence significantly affects behavioral intention to use mobile applications. However, this result aligns with research by Oliveira et al (2014) and Thaker et al (2019), which state that social influence does not affect user behaviour intention in mobile banking adoption.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The statistical test results show a p-value of 0.449 and a path coefficient value of -0.019, which indicates that H3 is rejected. These results contradict research from Nair et al (2023), which states that social influence significantly affects behavioral intention to use mobile applications. However, this result aligns with research by Oliveira et al (2014) and Thaker et al (2019), which state that social influence does not affect user behaviour intention in mobile banking adoption.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on research by Martins et al (2014) shows that PE, EE, and SI affect Behavioral Intention (BI). Other research from Nair et al (2023) states that only PE and EE are the main determinants of behavioral intention. Furthermore, research from Baptista & Oliveira (2015) found that EE, SI, and FC do not affect BI.…”
Section: Introductionmentioning
confidence: 98%
“…An important point for existing clients in Indonesia is the ease of use which is achieved by making lossless applications possible. This finding was supported by Chan et al (2022) and Nair et al (2022) that found a positive influence on effort expectancy to usage intention. Same result from Lisana (2022) that stated the de-gree of effort-free experience by customers will lead to a greater inclination to adopt the platform.…”
Section: Effort Expectancysupporting
confidence: 56%
“…The investors' behaviour in adopting online applications for e-trading and other investment decisions is affected by various factors. Some main factors influencing investors' behaviour are effort expectations, performance expectations, and perceived returns [ 45 ]. The perceived return and perceived risk were measured as significant forecasts of investors' adoption behaviour in the financial market [ 46 , 47 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…More significant revenue influences the stock market investors to invest in the financial market, and investors elect online platforms to generate and receive more revenue frequently [ 50 ]. Behaviour intention and facilitating conditions influence the adoption behaviour of investors through a mobile application for the online stock transaction and also found that future investors should consider these factors during mobile stock trading [ 45 ].…”
Section: Literature Reviewmentioning
confidence: 99%